A novel cotton WRKY gene, GhWRKY6‐like, improves salt tolerance by activating the ABA signaling pathway and scavenging of reactive oxygen species. Issue 4 (29th November 2017) - Ullah, Abid; Sun, Heng; Hakim,; Yang, Xiyan; Zhang, Xianlong
Abstract : WRKY transcription factors are transcriptional regulators of signaling pathways involved in biotic and abiotic stress responses. In this study, we report that ectopic expression of the GhWRKY6‐like gene significantly improved salt tolerance in Arabidopsis thaliana while silencing the GhWRKY6‐like increase the sensitivity to abiotic stresses in cotton. GhWRKY6‐like was localized to the nucleus. Expression of GhWRKY6‐like was remarkably induced by salt, polyethylene glycol (PEG) and abscisic acid (ABA) treatments. For further characterization, the GhWRKY6‐like gene was cloned and transformed into Arabidopsis . Our findings showed that the germination rate and root length were significantly improved in plants overexpressing GhWRKY6‐like vs wild type (WT) under salt, mannitol and ABA treatments. Additionally, the overexpressing lines showed greater salt tolerance than WT plants in soil. In addition, overexpressing plants accumulated less H2 O2 and malondialdehyde (MDA), while higher proline content, superoxide dismutase (SOD) and peroxidase (POD) activities were detected under salt and osmotic stresses. In contrast, virus‐induced gene silencing (VIGS) of GhWRKY6‐like in cotton showed enhanced sensitivity compared to WT plants during salt and drought stresses. Additionally, expression analysis of stress‐responsive genes in GhWRKY6‐like Arabidopsis revealed that there was increased expression of genes involved in the ABA signaling pathway ( AtABF4, AtABI5 and AtMYC2 ) and osmotic stress ( AtSOS2, AtRD29a and AtRD29b ). Our results revealed that GhWRKY6‐like enhanced salt tolerance in Arabidopsis by scavenging reactive oxygen species and regulating the ABA signaling pathway. We suggest that overexpression of the GhWRKY6‐like gene in cotton will enhance tolerance against salt, drought and osmotic stresses.